Implementasi Manajemen Perubahan Di MTS Negeri Di Kabupaten Sumedang Dalam Pencapaian Prestasi Institusi (Studi Pada MTS Negeri 3 Sumedang Dan MTS Negeri 8 Sumedang) - Taufiq Rahman (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
Implementation of change management at MTsN 3 and MTsN 8 Sumedang is necessary so that the Madrasah can improve and overcome problems and obstacles in the Madrasah so that the existence of the Madrasah becomes better than before. The change management process which includes planning, organizing, implementing, monitoring and evaluating aims to ensure that the implementation of change management at MTsN 3 and MTsN 8 Sumedang can run effectively and efficiently. The formulation of the research problem is how is the implementation of change management carried out at MTsN 3 and MTsN 8 Sumedang. What factors hinder the implementation of change management in achieving institutional achievements at MTsN 3 and MTsN 8 Sumedang? And how to overcome obstacles to implementing change management in achieving institutional achievements. The research method carried out was qualitative descriptive research. The data sources are Madrasah heads, Madrasah Committees, Madrasah Teachers and Madrasah Supervisors. Data collection techniques were carried out by observation, interviews, and documentation studies. From the research results, it was concluded that the implementation of change management at State MTs in Sumedang Regency still experiences many obstacles and requires solutions to achieve institutional achievements.